Ahlus Sunnah wal Jama’ah Value Internalization and Religious Moderation among Islamic University Students - Eka Fanda Saputra; Prima Cristi Crismono; Muhammad Ilyas; Harapandi Dahri (JURNAL AT-TURAS, 2026)
Religious polarization and the rise of exclusivist religious attitudes among young people present significant challenges for Islamic higher education institutions in promoting religious moderation. In the Indonesian context, the values of Ahlus Sunnah wal Jama’ah (Aswaja) including tawassuth (moderation), tawazun (balance), tasamuh (tolerance), and i‘tidal (justice) are widely recognized as a theological foundation for fostering moderate Islamic perspectives. However, empirical studies examining how the internalization of these values influences students’ religious moderation attitudes remain limited, particularly within Islamic higher education institutions. This study aims to analyze the effect of the internalization of Aswaja values on the religious moderation attitudes of students at the Islamic University of Jember. This research employs a quantitative approach with an explanatory design. A total of 155 students were selected using simple random sampling. Data were collected through a Likert-scale questionnaire measuring the internalization of Aswaja values and indicators of religious moderation attitudes, including tolerance, inclusivity, rejection of violence, and balanced religious practice. The data were analyzed using descriptive statistics and simple linear regression. The findings indicate that both the level of internalization of Aswaja values and students’ religious moderation attitudes are categorized as high. Regression analysis reveals that the internalization of Aswaja values has a positive and significant effect on students’ religious moderation attitudes (β = 0.63, p < 0.05), with a coefficient of determination (R²) of 0.40. These results demonstrate that the internalization of Aswaja values contributes substantially to shaping moderate, tolerant, and inclusive religious attitudes among students. This study provides empirical evidence supporting the strategic role of Aswaja-based educational approaches in strengthening religious moderation within Islamic higher education.